2020
DOI: 10.3389/fneur.2020.538257
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Possible Osteoporotic Conditions on the Recurrence of Chronic Subdural Hematoma

Abstract: The recurrence rate of chronic subdural hematoma (CSDH) has been reported to range from 2.3 to 33%. As bridging veins are composed of abundant collagen bundles and bone matrix, we aimed to investigate the possible associations between skull Hounsfield unit (HU) values and the recurrence of CSDH. We retrospectively enrolled patients with CSDH who underwent burr hole surgery. The HU values of the frontal skull were measured on brain CT scans. The cumulative hazard for recurrence was estimated according to predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…However, this study shows that antithrombotic use is not associated with CSDH recurrence. There are also some retrospective studies that have yielded similar results ( 10 , 36 , 45 , 46 ). Preoperative antithrombotic use does not seem to influence the rate of CSDH recurrence and early antithrombotic recommencement may reduce the risk of thromboembolic events ( 45 , 46 ).…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…However, this study shows that antithrombotic use is not associated with CSDH recurrence. There are also some retrospective studies that have yielded similar results ( 10 , 36 , 45 , 46 ). Preoperative antithrombotic use does not seem to influence the rate of CSDH recurrence and early antithrombotic recommencement may reduce the risk of thromboembolic events ( 45 , 46 ).…”
Section: Discussionmentioning
confidence: 80%
“…Radiological variables including preoperative hematoma width, preoperative midline shift, preoperative hematoma volume, postoperative residual air accumulation, CT imaging of different types of CSDH, and the residual total hematoma cavity volume have already been considered as predictive factors for CSDH recurrence ( 27 , 36 , 37 ). In the present study, gradation and separated types, PostRCV ≥70 ml, PostRAV ≥28 ml, PostRHV ≥55 ml, residual hematoma width ≥1.4 cm, postoperative midline shift ≥5.6 mm, and postoperative brain re-expansion rate <41% are risk factors of recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant correlation between the Hounsfield unit (Hu) values of the skull and bone mineral density has been previously established (7). Furthermore, it was reported that patients exhibiting lower bone mineral density are at a heightened risk of experiencing recurrent CSDH (8). As a result, we have formulated the hypothesis that skull density is correlated with the progression of CSDH.…”
Section: Introductionmentioning
confidence: 83%
“…Osteoporosis is a systemic disease that is strongly associated with genetic components of type 1 collagen [ 6 ]. Therefore, we previously hypothesized that low bone mineral density (BMD) would negatively influence the integrity of bridging veins, as veins are composed of smooth muscle cells [ 7 ]. Loss and degenerative changes in vascular smooth muscle cells negatively influence vascular strength, which can cause blood vessels to rupture easily [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%